Survey of mosquito species and mosquito-borne viruses in residential areas along the Sino–Vietnam border in Yunnan Province in China - Tian, Fengjuan; He, Jimin; Shang, Shanlin; Chen, Zhongyan; Tang, Yumei; Lu, Man; Huang, Changzhi; Guo, Xiaofang; Tong, Yigang (Frontiers in microbiology, 2023)
Mosquitoes are capable of carrying complex pathogens, and their feeding habits on the mammalian blood can easily mediate the spread of viruses. Surveillance of mosquito-based arbovirus enables the early prevention and control of mosquito-borne arboviral diseases. The climate and geography of Yunnan Province in China are ideal for mosquitoes. Yunnan shares borders with several other countries; therefore, there exists a high risk of international transmission of mosquito-mediated infectious diseases. Previous studies have focused more on the Sino–Laos and Sino–Myanmar borders. Therefore, we focused on the neighborhoods of Malipo and Funing counties in Wenshan Prefecture, Yunnan Province, China, which are located along the Sino–Vietnam border, to investigate the species of mosquitoes and mosquito-borne viruses in the residential areas of this region. This study collected 10,800 mosquitoes from 29 species of 8 genera and grouped to isolate mosquito-borne viruses. In total, 62 isolates were isolated and classified into 11 viral categories. We demonstrated a new distribution of mosquito-borne viruses among mosquitoes in border areas, including Tembusu and Getah viruses, which can cause animal outbreaks. In addition, Dak Nong and Sarawak viruses originating from Vietnam and Malaysia, respectively, were identified for the first time in China, highlighting the complexity of mosquito-borne viruses in the Sino–Vietnam border region. The awareness of the importance of viral surveillance and prevention measures in border areas should be further encouraged to prevent future outbreaks of potentially infectious diseases.